Metal Speciation in Sediment from Muara Angke, Jakarta Bay Using of BCR Sequential Extraction Procedure - Lestari Lestari; Fitri Budiyanto (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
The assessment of the biological availability of metals is rarely used only by knowing the total concentration of the metal. Therefore, six sediment samples from Muara Angke, Teluk Jakarta were assessed the chemical speciation of heavy metals. This study aims to determine metal speciation using the BCR sequential extraction procedure and to determine metal speciation to evaluate bioavailability in the sediments of Muara Angke, Jakarta Bay. In sediment from Muara Angke, the ability to move sequence of heavy metals studied was Pb>Zn>Cu>Ni. The mostly accumulated in the non-residual fraction of the total concentrations are Cu, Ni, Pb and Zn which indicated that the mobility and anthropogenic inputs of these metals in Muara Angke were quite high. The Risk Assessment Code (RAC) reveal that Zn and Ni at almost station exist in exchangeable and a fraction of carbonate-bound and therefore high-risk category. Most of the Cu at most of the station is in the oxidizable fraction, except a small portion found at all station is in the exchangeable fraction and fraction of carbonate-bound thus posing a low risk for the waters environment. The patterns of Pb speciation show no to low risk to the waters environment. However, metal observations in the waters are necessary because they are persistent and can accumulate which threatening the water environment.